FORMULATION AND IN VITRO EVALUATION OF ETHANOLIC EXTRACT OF POLYHERBAL FACE CREAM - SHIVATHAYA, NEHA; SURVE, RASHMI; SAWANT, RESHMA; KHOT, SUSHANT; BIRADAR, KISHOR; VERMA, RUCHIKA; GORAV, ANNAPURNA (International Journal of Current Pharmaceutical Research, 2022)
Objective: The aim of the present research work was to formulate and evaluate polyherbal face cream using ethanolic extracts of Aloe Vera gel, Neem, Turmeric and Mint. Methods: Extraction was done by the cold maceration technique. The cream was prepared by using the slab technique for homogeneous mixing of all the excipients and the herbal extracts. Three formulations of Oil in Water (O/W) type herbal cream were developed, namely F1, F2, and F3. Results: All the formulations were evaluated for various physical characteristics viz. pH 6.1-6.3, Spreadability 5-7.5gcm/sec, Viscosity 591-638 Cps, Extrudibility 2564-5102 g/cm2, good appearance and no phase separation was observed. Based on the results, F1 was found to be an optimized formulation with a smooth texture, good spreadability, extrudability and adequate viscosity. Stability studies as per ICH (International Council on Harmonisation) guidelines, revealed that the optimized formulation was stable at 25 °C±1 °C and 6% RH. Conclusion: Based on the results and discussion, the prepared formulations were found to be yellow in colour with a pleasant odour and smooth texture. All the formulations had almost constant pH, homogenous, emollient and non-greasy. As single plant extract possibly cannot increase the extent of efficiency of medicinal and cosmetic property compared to polyherbal plant extract. Considering that, we mixed polyherbal extracts to improve the cosmetic properties of the prepared polyherbal face cream. Hence it can be concluded that the cream was stable and can be safely used topically.